Crisis of the EU Eastern Policy - I. V. Bolgova (Vestnik MGIMO-Universiteta, 2014)
The results of the Vilnius summit of the EaP project and the consequent Ukrainian crisis with major international effects make possible questioning about the eventual scenarios of the EU eastern politics and possible configurations ofinternational interactions. The article elaborates on the key elements and trends of the EU activities at the post-soviet space that are likely to frame the context of its further developments. The most visible trends analysed here are the extreme differentiation of bilateral relations within the EaP project alongside with the growing symbolism of official rhetoric and program practices of the European Union. As a result, we see the EU's intention to narrow the geographical and qualitative field of its activities on the eastern directionwith saving the shell of the EaP for nominal functioning. Such tactics is not likely to result in a drastic change of the model of conflict dependencies in the "shared neighbourhood". The article analyses key misperceptions of the actors involved in the complex of interactions in the region. The structure is complicated by the deepening and widening of Russia-lead Eurasian integration project. Current crisis of the EU eastern policy is considered to derive from the exaggeration of the value-based, normative aspect of the common foreign policy in general and will have the systemic consequences both for the European external actions and for its internal developments.